Osteoarticular infections in infants under 3 months of age. Issue 1 (8th August 2022) - Branco, Joana; Duarte, Mariana; Norte, Susana; Arcangelo, Joana; Alves, Pedro; Brito, Maria; Tavares, Delfin; Gouveia, Catarina
Abstract: Background: Acute osteoarticular infections (OAI) in infants under 3 months of age (≤3M) are rare and remain a diagnostic challenge. Orthopedic complications and functional sequelae have been less well described in this age group. Our aims were to evaluate trends in aetiology, management, and outcomes of OAI ≤ 3M, and to compare these younger children who have OAI with older children. Methods: A longitudinal observational study was conducted of OAI cases admitted to tertiary care pediatric hospital from 2008 to 2018. OAI ≤ 3M was compared with children above 3 months. Clinical, microbiological, imaging, and outcome data were analyzed. Results: We identified 24 (9.1%) of the 263 OAI in children under 3 months. Analyzing OAI ≤ 3M there was a twofold increase since 2014; 54% were males with a median age of 28 days (IQR: 13.5–60.0), 10 (41.7%) were premature and nine (37.5%) had healthcare‐associated infections. Microbiological causes were identified in 87.5%, mostly Staphylococcus aureus (57.1%) and Group B Streptococcus (23.8%), and 25% were multidrug‐resistant (5 methicillin‐resistant S. aureus and 1 Enterobacter cloacae ). Bacteremia (100% vs 36.8%, P = 0.037), multidrug resistant bacteria (75% vs 16, P = 0.04), and healthcare‐associated infections (100% vs 26.3%, P = 0.014) were associated with sequelae. Comparing OAI ≤ 3M with older children, OAI ≤ 3M were treated with longer antibiotic courses, had more complications and sequelae (17.4% vs 3.2%, P = 0.002). Conclusions: S. aureus is still the most common cause of OAI ≤ 3M, and 25% of causative bacteria were multidrug‐resistant bacteria. Complications and sequelae were more frequent in OAI ≤ 3M when compared with older children.